ANALISIS FAKTOR âFAKTOR YANG BERPENGARUH TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN - Pinto, Eliza Xavier Soares; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to analyze some factors which have influenceto the timelinessof submitted financial statement of public company in Indonesia. These factors which have been tested in this research are profitability, liquidity, financial leverage, firm size, the reputation of accounting public office, and auditor opinion as the independent variable whereas the timeliness is the dependent variable. The samplesare 102 companies which are listed in Indonesia Stock exchange (IDX) and thesecompanies presenting their financial statement to the Capital Market Supervisory Agency (Bapepam) in 2012-2014 periods. The data is the secondary data. The sample selection has been done by using purposive method. The analysis instrument has been done by performing logistic regressions analysis with the significance level is 5%. The result of the hypothesis test shows that profitability, firm size, and the reputation of accounting public office have significant influence to the timelinessin submitting the financial statement. But, it has not been proven that the firm size and the reputation of accounting public office haveinfluence to the timeliness in submitting the financial statement.Keywords: timeliness, financial statement, profitability, firm size, the reputation of accounting public office.